Optimizing the Numbered Heads Together Method to Improve Mathematical Word Problem-Solving Skills in LCM Material - Damayanti, Firda; Winda Amelia (Journal of Practice Learning and Educational Development, 2026)
This study aims to improve students' ability to solve mathematical word problems (LCM). This study used the Classroom Action Research (Kemmis & McTaggart model) method, conducted in two cycles: Cycle I and Cycle II. The sample size for this study was 25 VA grade students at SDN Duren Tiga 09 Pagi, Pancoran District, South Jakarta. Qualitative and quantitative data analysis techniques were used, with data collection methods including tests, observation, and documentation. In the pre-cycle, the average score for students' ability to solve mathematical word problems (LCM) was 42.2, with a 4% completion rate, indicating the need for intervention. The results showed significant improvement: classical completion rate jumped from 48% in Cycle I to 100% in Cycle II, with an average final score of 86.8. NHT has proven effective because it successfully creates an active and collaborative learning environment while fostering individual responsibility, and is therefore recommended as a valid strategy for solving mathematical problems in elementary schools.